2011
DOI: 10.1016/j.juro.2011.01.034
|View full text |Cite
|
Sign up to set email alerts
|

The BMP-7–Smad1/5/8 Pathway Promotes Kidney Repair After Obstruction Induced Renal Injury

Abstract: PURPOSE Urinary tract obstruction causes hydroureteronephrosis and requires surgical intervention to prevent the development of permanent renal injury. While many studies have focused on the development of renal injuries, here we examine the molecular mechanisms that promote renal recovery following the correction of obstruction. MATERIALS AND METHODS A reversible murine model of ureteral obstruction was used to examine the BMP-7 and TGF-β signaling pathways during renal recovery following obstruction-induce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
53
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 49 publications
(56 citation statements)
references
References 24 publications
(39 reference statements)
2
53
0
1
Order By: Relevance
“…Furthermore, our previous studies demonstrated that treatment with exogenous BMP-7 during renal recovery promotes the repair of obstruction-induced renal injuries (14). These findings are supported by the findings of Zeisberg et al (27,28) that demonstrated that treatment with exogenous BMP-7 reverses the progression of chronic renal injury.…”
supporting
confidence: 67%
See 2 more Smart Citations
“…Furthermore, our previous studies demonstrated that treatment with exogenous BMP-7 during renal recovery promotes the repair of obstruction-induced renal injuries (14). These findings are supported by the findings of Zeisberg et al (27,28) that demonstrated that treatment with exogenous BMP-7 reverses the progression of chronic renal injury.…”
supporting
confidence: 67%
“…2, P Ͻ 0.01; 2 days UUO vs. 2 days UUO/10 days REC, n ϭ 3). The upregulation of BMP-7 is observed within 3 days following the correction of obstruction, the time period where the majority of repair also occurs (14). In contrast, BMP-7 levels remain suppressed during renal recovery following prolonged obstruction, even at 10 days following the correction of obstruction ( Fig.…”
Section: Unilateral Ureteral Obstruction As a Model System To Study Tmentioning
confidence: 94%
See 1 more Smart Citation
“…We and others have shown that Grem1 levels increase during DN whereas levels of BMP-7 decrease [33,46]. Strategies that stimulate BMP-7 signalling have been shown to attenuate renal fibrosis [5,[12][13][14][15][16][17], and reductions in Grem1 levels have a similar beneficial effect in mouse models of DN [32,37]. In vivo reduction of Grem1 via siRNA targeting recovered BMP-7 levels, suggesting that elevated Grem1 may have a role in repressing BMP-7 in DN [37].…”
Section: Discussionmentioning
confidence: 99%
“…Whereas BMP-4 has been shown to contribute to renal fibrosis, conflicting evidence exists for the pro-or anti-fibrotic role of BMP-2 in this process [8][9][10][11]. BMP-7 is thought of as anti-fibrotic, and has been the focus of many groups who demonstrated its anti-fibrotic activity in models of diabetic nephropathy and other kidney fibrotic diseases [5,[12][13][14][15][16][17]. To date, however, efforts to translate these data into BMP-7-centred treatment of fibrosis have been rather slow to develop [18,19] Canonical BMPs signalling involves the Smad pathway, where BMP dimers bind to type I and type II BMP receptors leading to the formation of a hexameric complex, triggering receptor phosphorylation.…”
Section: Introductionmentioning
confidence: 99%